Estudio de las interrupciones de servicio en el sistema de distribución mediante la gestión de mantenimiento en una empresa distribuidora y comercializadora de energía. - Vinueza Martínez, Ángel Rafael (2019)
At present, energy distribution and commercialization companies are looking for multiple alternatives to improve the quality of the electric service, and one of the most important points is the decrease in the number of interruptions that exist in the distribution system. It is for this reason, that in the present work of qualification will detail the diverse activities of predictive, preventive and corrective maintenance that realize in each one of the distinct functional stage of a company distribution, with a single main objective, that is the one of reduce the operations or interruptions that are generated in the electric service, taking into account that these variables (in reference to the number of interruptions) are of great contribution to reduce the impact that affects the technical quality service indicators such as the FMIK (average interruption frequency per KVA) and TTIK (total interruption time per KVA). In addition, a decision matrix will be displayed which uses variables of operations, load capacity and installed capacity to determine the number of feeders that have a greater number of failure or interruptions, and thus establish an order of priority in maintenance management develop.